A Critical Study on Raktapradoshaja Vikara with its Principle of Treatment (Mukhapaka) with Yastimadhu Churna. - Das, Anamika; Sahoo, Manoj Ku; Behera, Nabin Ku; Behera, Shibabrata (International Research Journal of Ayurveda & Yoga, 2022)
Introduction- As on today’s era, the changing lifestyle and eating pattern like Visamasana, Adhyasana, Ajirnasana & consumption of Virudhahara causes disturbance of the normal physiology which makes them prone to RaktaDushti Vikara, Mukhapaka is one of them. It is a painful and often recurrent inflammatory process of the oral mucosa seen commonly in all classes of society. Aim and Objectives - To study the efficacy of Yastimadhu churna in Mukhapaka on the basis of the principle of treatment of Raktapradoshaja Vikara (Shaman concept of Raktapittaharikriya). Materials and Methods- 30 no. of patients were selected and administered Yastimadhu Churna 5gm with luke warm water after food twice daily for a period of 15 days. All patients were investigated for Hb gm %, BSL before and after treatment. The collected data was distributed according to different demography and Prakriti Pareeksha. The assessment of the subjective and objective parameters was evaluated by the statistical w-test and paired t-test. Observation and result: - It has been observed that, the trial drug is statistically significant at level of 5% (p<0.5) to reduce both parameters. Discussion and Conclusion:-Finally it can be said that the trial drug could be best means for management of Rakta Pradoshaja Vikara (Mukhapaka). During the entire duration of therapy, any adverse effect of the drug was not found.